2021
DOI: 10.1097/iae.0000000000003116
|View full text |Cite
|
Sign up to set email alerts
|

Antivascular Endothelial Growth Factor Dosing and Expected Acuity Outcome at 1 Year

Abstract: Purpose: To determine the dose-response characteristics of the antivascular endothelial growth factor agents ranibizumab and aflibercept in neovascular age-related macular degeneration using published randomized trials and observational series.Methods: Literature review of published series from 2006 to 2018 as determined from electronic searches of PubMed and the Cochrane Library. Data extracted included treatment strategy, frequency, and first year visual acuity response. Monthly or bimonthly treatment schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 141 publications
(176 reference statements)
0
22
1
Order By: Relevance
“…Thus, the treatment outcome was relatively better in patients diagnosed in the later period, supporting the ndings of Holz et al 19 and Spaide. 12 In the present study, the number of injections was markedly higher in patients treated using the TAE regimen (mean 10.5) than that in patients treated using the as-needed regimen (mean 5.9). This result is consistent with those of previous studies showing higher injection frequencies for the TAE regimen compared to the as-needed regimen.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Thus, the treatment outcome was relatively better in patients diagnosed in the later period, supporting the ndings of Holz et al 19 and Spaide. 12 In the present study, the number of injections was markedly higher in patients treated using the TAE regimen (mean 10.5) than that in patients treated using the as-needed regimen (mean 5.9). This result is consistent with those of previous studies showing higher injection frequencies for the TAE regimen compared to the as-needed regimen.…”
Section: Discussioncontrasting
confidence: 41%
“…Spaide also recently con rmed the association between higher injection frequency and better visual outcome. 12 The primary nding of the present study was the higher injection frequency in patients diagnosed in the later period. This trend was observed regardless of the MNV type.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Several studies and treatment guidelines have suggested that proactive treatment strategies such as fixed dosing and treat-and-extend dosing strategies might result in better visual acuity outcomes than PRN dosing when treating patients with nAMD [ 8 , 9 , 10 , 11 , 12 ]. However, a recent systematic review has demonstrated that after adjusting for the number of intravitreal anti-VEGF injections, neither the treatment dosing regimen adopted, nor the anti-VEGF agent used, were significant predictors for visual acuity changes [ 13 ]. Nonetheless, other factors such as age, anatomical status of the retina, including the presence or absence of subretinal and/or intraretinal fluids, optical coherence tomography (OCT) central macular thickness, and macular morphology have been implicated as important prognostic factors in determining visual outcomes [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to several factors, particularly differences between real-world and clinical trial patient populations and differences in treatment frequency [ 11 ▪ ]. Notably, several studies, including large real-world studies [ 9 , 10 , 11 ▪ , 12 , 13 ▪ , 14 ] and a recent systematic review [ 15 ▪ ], found that dose frequency is a consistent indicator of vision outcomes, with real-world studies reporting average vision gains of zero to three letters with approximately five to seven injections in the first year of treatment.…”
Section: Introductionmentioning
confidence: 99%